Continuous Downstream Processing of Amino Acids in a Modular Miniplant. Issue 6 (23rd April 2018) - Hohmann, Lukas; Löbnitz, Lisa; Menke, Christina; Santhirakumaran, Bavatharani; Stier, Patrick; Stenger, Frank; Dufour, Fabrice; Wiese, Georg; zur Horst-Meyer, Santer zur; Kusserow, Burkhard; Zang, Werner; Nirschl, Hermann; et al.
Abstract: Global competition leads to a need for a fast time to market and increased resource efficiency. Continuous processing, module‐based plant design, and multipurpose equipment are recently discussed approaches for the fine‐chemical industry. As a representative, the downstream process of amino acid production is discussed herein. A conventional batch procedure was transferred to a continuous process and realized in a modular miniplant, which comprised of evaporation in a wiped‐film evaporator, seeded cooling crystallization in a coiled tubular crystallizer, and solid/liquid separation on a vacuum belt filter. The operations were realized on‐skid with individual automation systems and integrated sensors. L ‐Alanine was successfully processed in steady‐state operation. Abstract : Miniplants enable the demonstration and validation of process concepts and allow the generation of important information required for planning and scale‐up to pilot and production scale. A modular miniplant for the continuous downstream processing of model amino acid L ‐alanine has been designed. The miniplant is comprised of modules for evaporation, cooling crystallization, and solid/liquid separation.